Condições para o desenvolvimento de práticas de ensino em professores de empreendedorismo - Sangaletti, Andréia Peretti [UNESP] (2015)
The researches in Behavioral Analysis have shown improvements int he methodological procedures for teaching functional analysis for teachers. This study aimed to characterize the teaching conditions and behavioral measures of skills linked to an entrepreneurship module in vocational techinical course at secondary level and investigate whether the researcher interactions with the teacher to constitute instructional condition for the development of three components teaching repertoire: R1 = identication of behaviors that define the learning provided in the considered skills; R2 = planning conditions for the teaching of components behavior and for assessing the occurrence thereof under control of the planned relations; R3 = identification of correspondence between measures issued by the students in interaction with the conditions of teaching and evaluation prepared by the teacher and the descriptors that define the competencies deemed. The procedure was divided into four stages, which are subdivided into three steps. After the initial interview, was initiated Phase 1/Step 1 with the recording of lessons on the jurisdiction 1, editing the records, display the episodes the teachers and request for the same point whihc made the teaching and learning obatined by students. In phase 1/Step 2, we asked the teacher describing the corresponding actions of teaching and how students behaved front of their actions. In Phase 1/Step 3 the teacher could make estimated necessary changes in the text and in the next competence development plan. In phases 2 and 3, the procedures of steps 1,2 and 3 were replicated, this time considering the lessons relating to skills 5 (Phase 2) and 9 (Phase 3). In phase 4, the analysis of the teacher about the actions of the front students to available teaching conditions and relations with the repertoire required by the jurisdiction were recorded. Steps 1,2 and 3 Phase referred to the powers 1,5 and 9, respectively. The...